The Role of TICE in Improving Student Performance in Education: A Pathway to Enhanced Learning Outcomes - MOUMEN, Aziz; MAZOUAK ABDERRAZZAK (International Journal of Scientific Research and Innovative Studies, 2024)
The integration of Technologies de l'Information et de la Communication pour l'Éducation (TICE) has proven to be a transformative force in modern education, with the potential to significantly enhance student performance. TICE offer innovative ways to engage students, provide personalized learning experiences, and equip educators with powerful tools to assess and track progress. In Morocco, TICE have the potential to address longstanding educational challenges, such as disparities in access to resources, outdated teaching methods, and the need for more effective student engagement. This article explores how the strategic implementation of TICE can improve student performance by making learning more engaging, accessible, and tailored to individual needs. Through various case studies and practical examples, we examine how TICE are being used in classrooms to enhance understanding, motivate students, and provide teachers with effective tools to monitor and support student progress. Despite the challenges, such as infrastructure limitations and the need for adequate teacher training, TICE offers a path to achieving higher educational outcomes and preparing students for success in the 21st century【1-2】. Keywords: TICE, student performance, digital education, e-learning, digital literacy, teacher training, interactive tools, adaptive learning, educational equity, Morocco, technology in education, gamification, student engagement, learning outcomes. Received Date: July 07, 2024 Accepted Date: July 28, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/214